Diagnostic utility of special stains in defining the spectrum of maxillofacial pathologies - Akshay Gupta; Ankita Tandon; Saurabh Juneja; Nikita Gulati; Devi Charan Shetty (Indian Journal of Pathology and Microbiology)
Background: The Fine needle aspiration cytology (FNAC) is considered as a valuable and distinguished diagnostic test in the initial assessment of the patients presenting with a mass in the head and neck region or when a recurrence is suspected after previous treatment. Aims: This study was therefore designed to elucidate the efficacy of FNAC as an alternate diagnostic tool to histopathology in head and neck swellings and evaluation of staining efficacy of PAP and MGG stain over Haematoxylin and eosin (H and E) in routine cytopathological smears. Settings and Design: The study was conducted in the Department of Oral and Maxillofacial Pathology, where FNAC samples were collected from 150 patients with head and neck swellings. Materials and Methods: All the slides were stained with H and E, Papanicolaou (PAP), and May Grunewald Giemsa (MGG) stains. The cytopathological diagnosis was compared with histopathological diagnosis based on H and E stained sections obtained from paraffin-embedded formalin-fixed biopsy specimen of benign and malignant neoplasms. Statistical Analysis Used: The resulting data were analyzed using SPSS software version 19. Differences between the variables were analyzed using Pearson Chi-square test and Kruskal–Wallis test wherever applicable. Results: The FNAC as a diagnostic tool has sensitivity of 84.8%, 72.72%, and 78.78%, specificity of 62.5%, 75%, and 75%, and accuracy of 80.48%, 73.14%, and 78.04% in H and E, MGG, and PAP stain, respectively. PAP stain was the most efficient stain when all qualitative parameters are taken into consideration with maximum sensitivity and specificity for achieving definitive cytodiagnosis. Conclusions: The FNAC is an inexpensive and minimally invasive technique to diagnose different types of head and neck swellings and complement histopathological diagnosis.